2004
DOI: 10.1017/s0950268804002237
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of two Victoria and Yamagata influenza B lineages in Yamagata, Japan

Abstract: We attempted to predict epidemics of influenza B, focusing on B/Victoria/2/87-like (V) and B/Yamagata/16/88-like (Y) lineages, in Yamagata, Japan. We collected 9624 nasopharyngeal swabs for virus isolation from patients with respiratory infections between 1996 and 2003 and 237 sera for seroepidemiological analysis by haemagglutination-inhibition test in 2001. We isolated 424 V-lineage and 246 Y-lineage viruses during the study period. Three herald viruses in the 2000--2001 season enabled us to predict a V-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The shedding and transmission data suggested that the 2009 A(H1N1) is sufficiently fit to compete with the seasonal A(H1N1) virus. Because serological cross-reactivity between 2009 A(H1N1) and seasonal H1N1 viruses was found to be negligible (5), and different antigenic variants of influenza B viruses have coexisted for extended periods of time (22), the 2009 A(H1N1) influenza virus should be considered capable of continued cocirculation in the human population with the existing seasonal influenza viruses.…”
mentioning
confidence: 99%
“…The shedding and transmission data suggested that the 2009 A(H1N1) is sufficiently fit to compete with the seasonal A(H1N1) virus. Because serological cross-reactivity between 2009 A(H1N1) and seasonal H1N1 viruses was found to be negligible (5), and different antigenic variants of influenza B viruses have coexisted for extended periods of time (22), the 2009 A(H1N1) influenza virus should be considered capable of continued cocirculation in the human population with the existing seasonal influenza viruses.…”
mentioning
confidence: 99%
“…We published our first paper related to our microplate method focusing on enterovirus isolation in 2003 (18). We then published 3 papers related to Echo13, Ad7, and Flu B using virus isolation and serological techniques such as the NT test and HI test (31)(32)(33). These papers on Echo13 and Ad7 were our first studies related to emerging and re-emerging viral diseases, which later became an important theme in our research.…”
Section: Initial Work Between 2003 and 2005mentioning
confidence: 99%